Public Perception and Behavior Towards Leprosy in Endemic Areas Regency Touna - Devi Savitri Effendy; Intan Tiara; Indri Reva Wardani (Journal of Health Science and Pharmacy, 2025)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae and remains a public health concern in endemic areas, including Tojo Una-Una Regency. The high prevalence of leprosy in this region is closely associated with community perceptions and behaviors that are often influenced by stigma and misconceptions surrounding the disease. Central Sulawesi Province is classified as a high-endemic area for leprosy. Although since 2019 the prevalence has declined to below 1 case per 10.000 population, sustained surveillance and vigilance remain essential, as the average prevalence is still approximately 0.95 per 10.000 population. Furthermore, Central Sulawesi continues to report several leprosy pockets over the last three reporting periods. Objectives: This study aims to describe community perceptions and behaviors related to leprosy in the endemic area of Tojo Una-Una Regency and to analyze the prevalence of leprosy cases based on secondary data from 2022. Methods: A quantitative descriptive approach was employed using secondary data obtained from the 2022 Central Sulawesi Provincial Health Profile. Data were collected through document review and analyzed descriptively using tables and graphical presentations to illustrate leprosy prevalence. Results: The findings indicate that Tojo Una-Una Regency recorded the highest leprosy prevalence in 2022, at 2.36 per 10,000 population. This elevated prevalence is attributed to low levels of public awareness, persistent social stigma, and limited access to adequate health services and health education. Conclusion: Community misperceptions and behaviors play a significant role in sustaining the high prevalence of leprosy in Tojo Una-Una Regency. Therefore, leprosy control efforts in endemic areas must extend beyond medical interventions to include social, educational, and cultural approaches that actively engage communities. Integrated strategies involving health education, stigma reduction, strengthening of community health cadres, and improved access to health services are essential for sustainable leprosy control.